Calycosin-loaded nanoliposomes as potential nanoplatforms for treatment of diabetic nephropathy through regulation of mitochondrial respiratory function - Chunrong Huang; Lian-Fang Xue; Bo Hu; Huan-Huan Liu; Si-Bo Huang; Suliman Khan; Yu Meng (Journal of Nanobiotechnology, 2021)
Abstract Backgrounds One of the most common complications in diabetic nephropathy is generation of high levels of ROS which can be regulated by herbal antioxidants. However, polyphenols like calycosin, the bioactive compound of Radix astragali suffer from low solubility and poor bioavailability. Methods Therefore, in the present study, calycosin-loaded nanoliposomes were fabricated and characterized by TEM, DLS and FTIR techniques. Afterwards, the drug loading (DL) and entrapment efficiency (EE), drug release, solubility, stability, and pharmacodynamic assays were performed. Finally, the antinephropathic effects of calycosin-loaded-nanoliposomes on mitochondria of kidney cells were explored by MTT, ROS, MDA, mitochondrial respiratory function assays. Results The result showed that the size, hydrodynamic radius, zeta potential, EE, and DL were, 80 nm, 133.99 ± 21.44 nm, − 20.53 ± 3.57, 88.37 ± 2.28%, and 7.48 ± 1.19%, respectively. The outcomes of in vitro release assay showed that calycosin-loaded nanoliposomes were significantly slow-release in dialysis media with pH 1.2, pH 6.9 and pH 7.4, at about 30 min, the dissolution of calycosin from nanoliposome became almost complete, and after 2 months, the calycosin-loaded nanoliposomes were still stable. Pharmacokinetic assay revealed that the AUC0−t of calycosin in calycosin-loaded nanoliposome group was 927.39 ± 124.91 μg/L*h, which was 2.26 times than that of the free calycosin group (**P < 0.01). Additionally, the MRT0−t and t1/2 of calycosin in the calycosin-loaded nanoliposome group were prolonged by 1.54 times and 1.33 times than that of free calycosin group, respectively (*P < 0.05). Finally, it was shown that calycosin-loaded nanoliposomes regulated the viability, ROS production, lipid peroxidation and function of mitochondria in kidney cells of diabetic rats as a model of diabetic nephropathy. Conclusion In conclusion it may be suggested that new therapies based on nano-formulated calycosin can restore mitochondrial function which can improve diabetic nephropathy. Graphic abstract